2012
DOI: 10.1111/j.1460-9592.2012.03827.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose aprotinin, blood product transfusions, and short‐term outcome in neonates and infants: a pediatric cardiac surgery center experience

Abstract: No association was found between the prophylactic use of aprotinin, blood product transfusions, and short-term outcome in this population of neonates and infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The initial literature search resulted in 1,008 studies, of which 221 were used for full-text review. Sixty-eight articles, with a total of 28,735 patients, met inclusion criteria and were used in the analysis (3, 6, 7, 18–82). The PRISMA diagram describing the screening of studies is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The initial literature search resulted in 1,008 studies, of which 221 were used for full-text review. Sixty-eight articles, with a total of 28,735 patients, met inclusion criteria and were used in the analysis (3, 6, 7, 18–82). The PRISMA diagram describing the screening of studies is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Others have suggested that the use of aprotinin (currently not available in the United States) might lessen postoperative bleeding. 14,[24][25][26] In addition, given the independent association of blood transfusions and mortality, we stress the importance of weighing the risks and benefits of each transfused blood product, especially PRBCs, before administration. Their potential benefits, including increased oxygen carrying capacity and improved hemodynamics, have been well described 16,18 ; however, the adverse effects are an important consideration, even for patients with ongoing bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…10 Pediatric data have demonstrated an increased duration of mechanical ventilation and ICU length of stay in relation to blood transfusions, with no demonstrable survival benefit for aggressive transfusion strategies compared with conservative transfusion strategies. [11][12][13][14][15][16][17] The primary goal of the present study was to examine the relationship of early postoperative bleeding in infants with surgical mortality and adverse events. We hypothesized that increasing amounts of postoperative bleeding would be associated with an increased mortality risk and adverse events, including a prolonged duration of mechanical ventilation and ICU length of stay.…”
mentioning
confidence: 99%
“…11,14,15,20,26,33,[35][36][37][38] Of the two prospective observational studies, one left the choice for aprotinin to the discretion of the attending anaesthesiologist 16 and the other used a timed-based allocation method, 18 causing a high risk for selection bias. Discrete factors, such as physician bias regarding patient selection, 10,12,[21][22][23]25,31,39,42 choice of aprotinin use, 34,41 heterogeneous control group (TXA or no drug) with two different CPB circuits, 10 lack of standardised transfusion protocols 12,13,16,21,25,29,30,32,40,43 and lack of full blinding of surgical personnel and outcome assessors, 11,15,16,18,20,36 may account for some of the heterogeneity and conflicting effects observed in the observational and retrospective studies. Two studies 15,20 only applied blinding during surgery, resulting in an important risk of detection bias.…”
Section: Risk Of Bias Across Studiesmentioning
confidence: 99%